A pilot randomized controlled trial of complete bed rest versus activity restriction after preterm premature rupture of the membranes. (September 2019) - Martins, Inês; Pereira, Inês; Clode, Nuno
Abstract: Objective: To assess the impact of bed rest on maternal and neonatal outcomes in pregnancies complicated by preterm premature rupture of the membranes (PPROM), enabling proper sample size calculation for a powered randomized controlled trial (RCT). Study Design: We conducted a pilot unblinded randomized controlled trial with a 1:1 allocation ratio (complete bed rest vs activity restriction groups) on singleton pregnancies complicated by PPROM at 24 + 0–33 + 6 weeks. Maternal and neonatal data were compared between groups with an intent-to-treat analysis. The primary outcomes were the latency time to delivery and the incidence of chorioamnionitis. The trial was conducted in a tertiary center of the Portuguese national healthcare system. Patients received standard antibiotic prophylaxis. Delivery was planned for the 34th week of gestation, except in cases of spontaneous labor or another complication. Results: Thirty-two cases were randomized and analyzed, 14 in the complete bed rest group and 18 in the activity restriction group. The median gestational age at PPROM was 30 vs 29 weeks (p = 0.82). In the complete bed rest group, the incidence of chorioamnionitis was nonsignificantly lower (14% vs 28%, p = 0.43). Median latency time was 11.5 days (95% CI, 2–20) in the complete bed rest group and 7.5 days (95% CI, 3–11) in the activity restriction group, lacking statistical significance on univariate (p = 0.6) and survival analyses (log-rank test, p = 0.75). No difference was found between groups regarding indication or type of delivery and maternal or neonatal morbidity. The median gestational age at delivery was 32 weeks for both groups (p = 0.94). A sample size of 2052 participants was calculated for a powered RCT, considering latency as the primary outcome. Conclusion: In this pilot trial, bed rest did not increase latency to delivery and did not improve maternal or neonatal morbidity in the setting of PPROM at 24 + 0–33 + 6 weeks. A sample size calculation is now available for a powered RCT.